Effectiveness and reliability of percutaneous microwave ablation therapy in early stage renal cell cancer: Intermediate term results - Ateş, Ömer Faruk (Journal of Surgery and Medicine, 2020)
Aim: Percutaneous tumor ablation is the most important alternative to surgery in early stage renal cell cancers (RCC). Although many studies are conducted with radiofrequency ablation and cryoablation therapy in RCC, the data regarding microwave ablation (MWA) is more limited. In this study, we aimed to evaluate the efficacy of percutaneous MWA in the treatment of RCC, its safety in terms of residual renal function and other complications, and its clinical results. Methods: In T1b patients, the suitability for MWA was evaluated with a urologist based on characteristics such as size, and location of the mass (intestinal proximity, proximity to the main renal vascular structures and renal pelvis). Fourteen T1a, five T1b and one T2 RCC patients treated with MWA were included in this retrospective study. MWA was preferred when partial nephrectomy was highly risky or contraindicated due to medical comorbidities or the patients refused to undergo surgical treatment. The patients were ablated with uncooled MWA device with 30W energy under sedation or general anesthesia under ultrasound guidance for an average of 13 minutes. Multiple antennas were used for masses larger than 4 cm. Hydrodissection with saline was performed in cases where there was a non-target organ adjacent to the lesion. Lesion size, location of the lesion, ablation time, complications, Charlson comorbidity index, Hb, and creatinine values were recorded. Patients were followed by CT. Results: The mean age of the patients was 68.9 years, and the median lesion size was 2.8 cm. While the tumor was exophytic in 12 patients, it was intraparenchymal or endophytic in 8 patients. The average Charlson comorbidity index score of the patients was 6.9. Technical success was achieved in all patients. Average ablation time was 13 minutes. Minor complications occurred in 3 patients. The median follow-up period of the patients was 13.5 months. In Kaplan Meier analysis, progression-free survival was 12 months. During follow up, distant organ metastasis was not observed in any of the patients, recurrence was observed in 2, and no patients died. Conclusion: MWA can be applied in early stage RCCs with very high technical success. The results of our study show that MWA is effective and highly reliable in RCCs. It can be safely applied, especially in patients who are not suitable for surgery and in residual RCCs.